Impact of persistent antigenic challenges and splenectomy on immune cells in β-Thalassemic patients. - Sonia Elia Ishaq; Taban Kamal Rasheed; Dara K. Mohammad (Zanco Journal of Pure and Applied Sciences, 2022)
Infection is common in thalassemia patients and is one of the leading causes of death. It's still unclear why these individuals are so sensitive to infection. There is strong evidence that a deficiency in the functioning of phagocytic cells plays a key role in the weakened resistance to pathogenic bacteria. The purpose of this study was to investigate the function of phagocytic cells by comparing the serum levels of granulocyte macrophage-colony stimulating factor (GM-CSF) and Neopterin in thalassemia patients to healthy people. The study included 50 thalassemia patients and 30 healthy controls. Enzyme-linked immunosorbent assay (ELISA) was applied to estimate the serum levels of GM-CSF and Neopterin. Serum levels of GM-CSF were significantly elevated in thalassemia patients when compared to healthy people (p < 0.05), while serum levels of Neopterin showed no significant change between thalassemia patients and healthy controls. Both serum levels of GM-CSF and Neopterin showed no significant difference between Splenectomized and healthy controls. Total leukocyte counts, lymphocytes, MID (monocytes), platelets, and RBC were all significantly higher in thalassemia patients compared to healthy controls. But, granulocyte counts showed no significant difference between the thalassemia patients and the healthy controls. On the other hand, total leukocytes, monocytes, lymphocytes and platelets counts were significantly raised in splenectomized patients when compared to healthy controls and non-splenectomized patients, respectively. We came to the conclusion that thalassemia patients have a high immune cell count, which is most likely due to the antigenic difficulties posed by blood transfusions. On the other hand, these patients have an impaired immune system.